2012
DOI: 10.1111/j.1756-185x.2012.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical pattern of juvenile idiopathic arthritis in a semi‐urban area of Bangladesh

Abstract: Prevalence of JIA in this study in a semi-urban area of Bangladesh was consistent with established population-based studies in developed countries. Clinical pattern of JIA patients also had similarities with reports from Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The possibilities are further substantiated by the fact that majority (60%) of the patients from a community based study reported from our center in Bangladesh had oligo-articular JIA. 14 In that community based study sex ratio was also different, girl: boy ratio being about 2:1.…”
Section: Discussionmentioning
confidence: 91%
“…The possibilities are further substantiated by the fact that majority (60%) of the patients from a community based study reported from our center in Bangladesh had oligo-articular JIA. 14 In that community based study sex ratio was also different, girl: boy ratio being about 2:1.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, diseases like cancer, Chikungunya or arthritis are common in Bangladesh and these diseases can cause chronic pain. [3,5] Pain is usually treated with drugs like aspirin or paracetamol; chronic and severe pain may need opioid drugs for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the absence of a unified registration in many countries, populations or hospitals prevents more accurate collection of epidemiological data. However, over recent decades, several population studies have been conducted in different countries, with different methodologies depending on the structure of each locality [10][11][12][13][14][15][16][17][18][19]. The objective of most of these studies is to assist in planning the structure of health services for the care of suspected and diagnosed cases [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, several methodologies have been used to determine the prevalence of JIA. However there is no design standardization in this various international studies [10][11][12][13][14][15][16][17][18]. Different methods have been used to obtain the prevalence, including data collection through population and hospital databases, questionnaires or interviews with professionals in health centers or parents/caregivers and physical examinations in the sample as a whole.…”
Section: Introductionmentioning
confidence: 99%